Analysis of public grants and state aids given by the Spanish National Sports Council - Munoz-Llerena, A.; Caballero-Blanco, P.; Gomez-Chacon, R. (Journal of Physical Education and Sport, 2018)
Problem Statement: Nowadays, sports is a phenomenon that has a great impact on today`s society. In Spain, its main government institution is the National Sports Council (NSC), which concedes sports grants and aids. Approach: to analyze the available data of the different public calls made by the NSC. Purpose: to observe and evaluate the evolution of those public calls over time to define the current situation of grants and public aids in sports-related issues given by the Spanish government. Results: an investment of 136,796,793.05€ was made on sports federations between the years 2014 and 2017, in addition to 5.045.000€ on the Women and Sports program; 13,129.84€ have been used since 2015 in 66 social aids for sportswomen; 81,552.48€ have been allocated to grants for sports federation directors; national school and university tournaments have been subsidized between 2014 and 2017 with 1,071,741.84€ and 355,387.12€, respectively; autonomous communities have been granted 2.520.000€ since 2014 for sports technification centers; payments of 930,523.98€ have been made between 2011 and 2012 to foster researching activities, scientific actuations and periodical publications in the sports field; for acts against violence, racism, xenophobia and injustice 589,137€ were granted between 2009 and 2011; public universities and entities and nonprofit organizations received aids of 523,396.78€ and 81,421.99€, respectively, in 2010; 7,500,000€ have been allocated since 2014 to registered grants; and the P+S plan was funded in 2010 and 2011 with 91,000€. Conclusions: Public calls made by the NSC are focused on sports federations, setting research aside and supporting gender equality.